E-Marketing Learning Media Based on Local Wisdom of Sambas Songket Weaving - Nurleni Nurleni; Junaidi Junaidi; Nuraini Asriati (Journal of Innovation in Educational and Cultural Research, 2023)
This study intends to provide ways to help teachers and students solve problems to increase the competency skills of students to develop retail businesses independently. The research objective is to examine the development of e-marketing learning media based on the local wisdom of Sambas Songket weaving in the X Marketing Programme in a public school. The research procedure used the ADDIE Research and Development model. Data collection techniques included observation, tests, interviews, questionnaires, and documentation. The research results show that 1) Students need interesting learning by using e-marketing learning media based on the local wisdom of Sambas Songket weaving; 2) The media are created using the Google Sites, Google Drive, Canva, and YouTube applications; and 3) validation of design expert n = 0.741 in a good category, media expert n = 0.879 in a good category, and material expert n = 0.821 in a good category. Individual student responses are n = 88.57% positive, small groups 97.38% very positive, and field tests 97.09% very positive; 4) The average result of the pretest was 52.19 and the posttest was 73.75, meaning that there was an increase of 21.56; 5) The results of the analysis, sig value (2-tailed) 0.00 0.05, then Ha is accepted. The products are proven to help students and teachers in learning, as well as students having thoughts about promoting Sambas Songket weaving.